Learning styles and online learning satisfaction of University students during COVID-19 pandemic - Ahmad, Norfadzilah; Alias, Anis Nur Fathihah; Wan Mamat, Wan Hasliza; Atan, Ashikin (2022)
Background: Learning styles can be defined as factors, behaviours, and attitudes that aid the learning process. It benefits students as it allows a better understanding of the lesson. Purpose: This study aims to identify the learning styles and satisfaction of online learning of health sciences-based students at the International Islamic University Malaysia during the COVID-19 pandemic. Methods: A quantitative cross-sectional study with convenience sampling was conducted among 260 students from April to June 2022. Data were gathered using Google Forms and a self-administered questionnaire, available in English and distributed to the Kulliyyah of Nursing, Kulliyyah of Allied Health Science, Kulliyyah of Pharmacy, Kulliyyah of Medicine, and Kulliyyah of Dentistry students. The questionnaire was adopted and adapted from two sets of questionnaires, i.e., two sets from the Felder and Soloman Index Learning Styles and one set of satisfaction questionnaires from Aritino (2008). Data analysis was done using SPSS version 26.0. Results: Most respondents chose the visual, sensing, and sequential learning styles, while an almost balanced proportion chose activist-reflective. Most of them have high levels of satisfaction with online learning. Conclusion: Students prefer the Visual, Sensing, and Sequential learning styles and have high levels of online learning satisfaction.